ACCEPTANCE TESTING ON A MULTIPLE-DETECTOR SPECT SYSTEM - KRISANACHINDA, Anchali (The ASEAN Journal of Radiology, 2023)
Single Photon Emission Computed Tomography (SPECT) system is a nuclear medicine imaging device using a rotating scintillation camera and a computer system to acquire, reconstruct and process a patient tomographic images in transverse-axial, coronal and sagittal planes. The system can have one detector or more. The advantage of multiple detectors is the higher sensitivity, shorter time study and the ability to perform more patient studies per day. Acceptance testing of the SPECT system by the physicist is an important step towards the acquiring of images of the highest possibility quality over the operating life of the instrument. The test should be performed after the system is installed, carefully tuned, clinical operative, and before patient studies are initiated. The major purpose of the acceptance test is to assure the user that the system is performing according with the specifications as quoted by the manufacturer. The National Electrical Manufacturers Association (NEMA) has prepared a protocol detailing test conditions to be used by manufacturers. The document provides specific protocol to measure the performance parameters and traceability from manufacturer to user. Two test methods, performance standards and class standards are measured in the acceptance testing which include the intrinsic and system resolution, spatial linearity, energy resolution, flood field uniformity sensitivity and count rate performance. Furthermore, whole body imaging, multiple window spatial registration (MWSR) must be included that in the acceptance test of single and multiple detectors. SPECT phantom study, will offer the information on the SPECT performance in terms of tomographic uniformity, contrast, resolution and lesion detectability. Images should be compared from each detector and all detectors. Best image quality should be obtained from all detectors. In this paper, the result of the acceptance test of the triple detector SPECT, TRIAD XLT 20 will be presented. All the results are within acceptable limit under NEMA Standards and manufacturer guidelines. The acceptance testing of a system isa critical step towards the achievement of high quality performance of any damage, deficiencies or flaws before the warranty has expired. No instrument should be put into routine use unless it has been shown through acceptance testing to be performing optimally. An instrument that does not perform correctly at installation has a high likelihood of never doing so.